Post-Coronavirus Disease-2019 Rhino-orbital Mucormycosis: A Case Report - Shrestha, Tina; Parajuli, Sanket; Keshari, Rajani; Kharbuja, Punyaram; Sharma, Sadhana; Shrestha, Jeevan Kumar (Nepalese Journal of Ophthalmology, 2023)
Background: Rhino-orbital-cerebral mucormycosis (ROCM) is a rare, opportunistic, angio-invasive, and fatal infection caused by mold fungi of the genera Rhizopus, Mucor, and Rhizomucor. The global incidence of ROCM is 0.005-1.7 per million, with a fatality rate of 46%. Early diagnosis and treatment are crucial for this disease, as a delay of one week can increase the mortality rate to 66%. Case: A 32-year-old male, a known case of coronavirus disease 2019 (COVID-19) for the past 15 days from Janakpur, Dhanusha, Nepal presented to the emergency department of Dhulikhel Hospital with a sudden onset of blurred vision in the left eye, left-sided ocular pain, and nasal bleeding for the last three days. Observations: The patient was suspected of post-COVID-19 mucormycosis, and a nasal swab for potassium hydroxide (KOH) mount showed hyphae in microscopy. Intravenous and retrobulbar liposomal amphotericin B were administered as medical therapy, along with surgical debridement. A multidisciplinary approach was necessary for the treatment. Conclusion: A long-term, multimodal treatment approach involving combined antifungal drug therapy (intravenous liposomal amphotericin B and retrobulbar amphotericin B), and timely surgical debridement leads to an improvement in both short-term and long-term outcomes.